2012
DOI: 10.5812/hepatmon.5969
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis Viruses B, C, D and HIV Infection Among Hemodialysis Patients in Kerman Province, South-East Iran

Abstract: BackgroundThe prevalence of hepatitis viruses in hemodialysis patients has been reported to be much greater than in the general population. Attention to local data, effectively guides health planners so that they can control infections and prevent nosocomial transmissions.ObjectivesThis cross sectional study was carried out to determine the prevalence of hepatitis B (HBV), hepatitis C (HCV), and hepatitis D (HDV) viruses, as well as the human immunodeficiency virus (HIV) in dialysis centers in the Kerman Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 17 publications
13
49
3
1
Order By: Relevance
“…On the other hand, 14 Studies carried out in various centers worldwide among dialysis patients have shown a prevalence of HCV as 8% -36% in North America, [16] 25% -39% in South America, [17] 1% -36% in Europe, [18] 17% -51% in Asia, [4] 1.2% -10% in New Zealand and Australia, [4] [16] and 7% -85% in South Africa [2] have reported that among patients on hemodialysis 5.9% were HCV positive while, 1.4% patients had HBV infection and 3.7% had infection with HBV and HCV [12]. Chandra et al have reported that among the patients of chronic kidney disease, renal transplant orhemodialysis, HBV, HCV and infection of both viruses were 7.46% and 37.10% respectively these results are not agreement to the results of our study [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 14 Studies carried out in various centers worldwide among dialysis patients have shown a prevalence of HCV as 8% -36% in North America, [16] 25% -39% in South America, [17] 1% -36% in Europe, [18] 17% -51% in Asia, [4] 1.2% -10% in New Zealand and Australia, [4] [16] and 7% -85% in South Africa [2] have reported that among patients on hemodialysis 5.9% were HCV positive while, 1.4% patients had HBV infection and 3.7% had infection with HBV and HCV [12]. Chandra et al have reported that among the patients of chronic kidney disease, renal transplant orhemodialysis, HBV, HCV and infection of both viruses were 7.46% and 37.10% respectively these results are not agreement to the results of our study [19].…”
Section: Discussionmentioning
confidence: 99%
“…17 This observation was in agreement with previous reports in Palestine, Moldavia, and other studies from different regions of the world. [20][21][22][23] Duration of dialysis is an important risk factor for acquiring infections as it is related to nosocomial transmission and dissemination of the infections in the dialysis units. 17 While analyzing patients who seroconverted, number of blood transfusions received significantly contributed to development of either hepatitis B or C infection in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Seroprevalence studies on triple hepatitis virus infections usually involve blood donors or patients with chronic liver diseases, but these do not represent the whole population. [15][16][17][18][19] In the state of Acre in Brazil, the seroprevalence rates for HBV and HDV are approximately 3.4% and 1.7%, respectively. 20 The biomolecular prevalence of HCV RNA within the population is estimated as 2.5%, and 0.05% of the same population will express concomitant markers, namely HCV RNA, HBsAg and antibodies against HDV.…”
Section: Prevalence Of Triple Hepatitis Infection: Global and Local Smentioning
confidence: 99%